Gauging the quality and trustworthiness in the citation practices of Malaysian academic researchers - Abrizah, Abdullah; Nicholas, D.; Badawi, F.; Kassim, N.A. (University of the Punjab, 2016)
The origin of this research is illuminated by CIBER’s exploratory research on Trust in Scholarly Communications conducted in 2012-2013. This study’s interest lies with Malaysian academic researchers both as producers and consumers and how they deal with the quality and trust consequences of the digital transition, especially, but not exclusively, the impact of social media and open access publishing on their scholarly communications. This paper reports on a survey on citation behaviour, part of a wider study of gauging quality and trustworthiness in scholarly communication in the emerging digital environment. It focuses on investigating what Malaysian researchers trust or find reliable to cite in their publications. In order to make the study results comparable, we adapted the same questionnaire that CIBER has developed and used in previous surveys. We used surveymonkey.com. a web-based questionnaire which has been widely used for surveys. The questionnaire went online on the 1 October 2014 and closed on the 30 December 2014. More than 400 respondents completed the questionnaire. The answers were analysed quantitatively and then grouped under descriptive headings of the types of reasons for citation provided. Similar to CIBER’s study, the motivations for citing were found to be complex and multi-faceted but, in nearly all cases, researchers do regard the authority and trustworthiness of the cited source as an important factor in choosing to cite it. Citing behaviour includes an acknowledgement of useful intellectual content, and this process cannot be separated from the researcher’s position in networks of trusted social and research influence. The digital transition has provided tools to help maintain and develop these social networks and it has also made it easier for researchers to investigate the credentials of the sources of documents. Peer-reviewed journals still hold influential. Measures of establishing trust and authority do not seem to have changed profoundly in Malaysia. The digital environment may bring ease and convenience to scholarly communication, but it gives more pressure for scholarly communication on high quality platforms. Looking at the researchers’ trust-related views, it is emphasised that academic librarians apply their understanding of scholarly communication towards delivering the right services to meet the needs of the academic community.